2017
DOI: 10.1021/acsmedchemlett.7b00157
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of Fevipiprant (NVP-QAW039), a Potent and Selective DP2 Receptor Antagonist for Treatment of Asthma

Abstract: Further optimization of an initial DP receptor antagonist clinical candidate NVP-QAV680 led to the discovery of a follow-up molecule 2-(2-methyl-1-(4-(methylsulfonyl)-2-(trifluoromethyl)benzyl)-1-pyrrolo[2,3-]pyridin-3-yl)acetic acid (compound , NVP-QAW039, fevipiprant), which exhibits improved potency on human eosinophils and Th2 cells, together with a longer receptor residence time, and is currently in clinical trials for severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…6 Fevipiprant is in clinical development for the treatment of asthma. [6][7][8] ILC2s were isolated from blood of healthy participants and expanded in vitro by mixed lymphocyte reactions to characterize the ILC2-intrinsic inhibitory effects of fevipiprant on DP 2 signaling (see Fig E1 and the Materials and Methods section in this article's Online Repository at www.jacionline.org). ILC2 migration toward PGD 2 (200 nmol/L) was measured by using IncuCyte live-cell microscopy (IncuCyte ZOOM; Essen Bioscience, Ann Arbor, Mich).…”
Section: Fevipiprant a Selective Prostaglandin D 2 Receptor 2 Antagomentioning
confidence: 99%
See 1 more Smart Citation
“…6 Fevipiprant is in clinical development for the treatment of asthma. [6][7][8] ILC2s were isolated from blood of healthy participants and expanded in vitro by mixed lymphocyte reactions to characterize the ILC2-intrinsic inhibitory effects of fevipiprant on DP 2 signaling (see Fig E1 and the Materials and Methods section in this article's Online Repository at www.jacionline.org). ILC2 migration toward PGD 2 (200 nmol/L) was measured by using IncuCyte live-cell microscopy (IncuCyte ZOOM; Essen Bioscience, Ann Arbor, Mich).…”
Section: Fevipiprant a Selective Prostaglandin D 2 Receptor 2 Antagomentioning
confidence: 99%
“…Phase II studies showed fevipiprant to be effective in patients with uncontrolled eosinophilic asthma, patients with severe airflow limitation, and patients with low-dose steroid-resistant allergic asthma. [6][7][8] An advantage of targeting inflammation upstream of ILC2s, rather than anti-type 2 cytokine therapies, is intervention earlier in the pathway and reduction in redundancy between type 2 effector cytokines. Furthermore, blockade of PGD 2 signaling will additionally target non-ILC2 DP 2 1 populations, such as T H 2 cells, T C 2 cells, basophils, and eosinophils, all of which have been implicated in asthma immunopathology.…”
Section: Fevipiprant a Selective Prostaglandin D 2 Receptor 2 Antagomentioning
confidence: 99%
“…Eosinophil activation is also associated with increased cytokine production, which has various downstream immunomodulatory effects [ 54 ]. DP 2 receptor activation at the eosinophil surface facilitates the trans-endothelial migration and influx of eosinophils, increases eosinophil degranulation and induces eosinophil shape change [ 40 , 55 , 56 ]. Eosinophil shape change in response to DP 2 activation [ 57 ] is similar to that visualised previously with eotaxin stimulation [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of eosinophils by DP2 has also been demonstrated in a number of studies. Those studies showed that PGD 2 signaling through DP2 on the surface of eosinophils could lead to shape change and promote degranulation and cytokine production (Gervais et al, 2001; Pharmacology of GPCRs in Asthma Therapy and Drug Action Sykes et al, 2016;Sandham et al, 2017). In addition, type 2 cytokines induced by DP2 signaling can have positive effects on the activation and migration of eosinophils, further contributing to excessive inflammation.…”
Section: Structural Insights Into Drug Actionmentioning
confidence: 99%